Identification of CACNA1D variants associated with sinoatrial node dysfunction and deafness in additional Pakistani families reveals a clinical significance. - Liaqat, Khurram; Schrauwen, Isabelle; Raza, Syed Irfan; Lee, Kwanghyuk; Hussain, Shabir; Chakchouk, Imen; Nasir, Abdul; Acharya, Anushree; Abbe, Izoduwa; Umair, Muhammad; Ansar, Muhammad; Ullah, Irfan; et al. (J Hum Genet, 2019)
Sinoatrial node dysfunction and deafness (SANDD) syndrome is rare and characterized by a low heart beat and severe-to-profound deafness. Additional features include fatigue, dizziness, and episodic syncope. The sinoatrial node (SAN) drives heart automaticity and continuously regulates heart rate. The CACNA1D gene encoding the Ca1.3 protein expressed in inner hair cells, atria and SAN, induces loss-of-function in channel activity and underlies SANDD. To date, only one variant c.1208_1209insGGG:p.(G403_V404insG) has been reported for SANDD syndrome. We studied five Pakistani families with SANDD and characterized a new missense variant p.(A376V) in CACNA1D in one family, and further characterized the founder variant p.(G403_V404insG) in four additional pedigrees. We show that affected individuals in the four families which segregate p.(G403_V404insG) share a 1.03 MB haplotype on 3p21.1 suggesting they share a common distant ancestor. In conclusion, we identified new and known variants in CACNA1D in five Pakistani families with SANDD. This study is of clinical importance as the CACNA1D founder variant is only observed in families from the Khyber Pakhtunkhwa (KPK) province, in Pakistan. Therefore, screening patients with congenital deafness for SAN dysfunction in this province could ensure adequate follow-up and prevent cardiac failure associated with SAN.
Keywords: Adolescent; Calcium Channels, L-Type; Deafness; Female; Heart Diseases; Humans; Male; Mutation; Pakistan; Pedigree; Prognosis; Sinoatrial Node

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly. - Ullah, Irfan; Kakar, Naseebullah; Schrauwen, Isabelle; Hussain, Shabir; Chakchouk, Imen; Liaqat, Khurram; Acharya, Anushree; Wasif, Naveed; Santos-Cortez, Regie Lyn P; Khan, Saadullah; Aziz, Abdul; Lee, Kwanghyuk; et al. (Hum Genet, 2019)
Postaxial polydactyly (PAP) is a common limb malformation that often leads to cosmetic and functional complications. Molecular evaluation of polydactyly can serve as a tool to elucidate genetic and signaling pathways that regulate limb development, specifically, the anterior-posterior specification of the limb. To date, only five genes have been identified for nonsyndromic PAP: FAM92A, GLI1, GLI3, IQCE and ZNF141. In this study, two Pakistani multiplex consanguineous families with autosomal recessive nonsyndromic PAP were clinically and molecularly evaluated. From both pedigrees, a DNA sample from an affected member underwent exome sequencing. In each family, we identified a segregating frameshift (c.591dupA [p.(Q198Tfs*21)]) and nonsense variant (c.2173A > T [p.(K725*)]) in KIAA0825 (also known as C5orf36). Although KIAA0825 encodes a protein of unknown function, it has been demonstrated that its murine ortholog is expressed during limb development. Our data contribute to the establishment of a catalog of genes important in limb patterning, which can aid in diagnosis and obtaining a better understanding of the biology of polydactyly.
Keywords: Animals; Consanguinity; Family Health; Female; Fingers; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice, Inbred C57BL; Mutation; Pedigree; Phenotype; Polydactyly; Toes; Whole Exome Sequencing

Confirmation of the Role of DHX38 in the Etiology of Early-Onset Retinitis Pigmentosa. - Latif, Zahid; Chakchouk, Imen; Schrauwen, Isabelle; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Abbe, Izoduwa; Acharya, Anushree; Jarral, Afeefa; Ali, Imran; Ullah, Ehsan; Khan, Muhammad Nasim; Ali, Ghazanfar; et al. (Invest Ophthalmol Vis Sci, 2018)
Purpose: Retinitis pigmentosa (RP) is a genetically heterogeneous trait with autosomal-recessive (ar) inheritance underlying 50% of genetic disease cases. Sixty-one arRP genes have been identified, and recently, DHX38 has been reported as a potential candidate gene for arRP with only a single family reported with a variant of unknown significance. We identified a missense variant in DHX38 that co-segregates with the arRP phenotype in two Pakistani families confirming the involvement of DHX38 in the etiology of early-onset RP. Methods: Exome sequencing was performed using two DNA samples from affected members of Pakistani families (MA88 and MA157) with early onset arRP. Sanger sequencing of DNA samples from all family members confirmed the segregation of candidate variant within both families. Results: A novel missense DHX38 variant c.971G>A; p.(Arg324Gln) was identified which segregates with the arRP phenotype and yielded a logarithm of the odds (LOD) score of 5.0 and 4.3 for families MA88 and MA157, respectively. This variant is predicted to be conserved and deleterious by several bioinformatics tools. Conclusions: We identified a second deleterious DHX38 variant that segregates with arRP in two families, providing additional evidence that DHX38 is involved in RP etiology. DHX38 encodes for pre-mRNA splicing factor PRP16, which is important in catalyzing pre-mRNA splicing.
Keywords: Adolescent; Adult; Cataract; Computational Biology; DEAD-box RNA Helicases; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; Humans; Male; Mutation, Missense; Nucleotide Mapping; Ophthalmoscopy; Pedigree; Retinitis Pigmentosa; RNA Splicing Factors; Sequence Analysis, DNA; Whole Exome Sequencing; Young Adult

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability. - Santos-Cortez, Regie Lyn P; Khan, Valeed; Khan, Falak Sher; Mughal, Zaib-Un-Nisa; Chakchouk, Imen; Lee, Kwanghyuk; Rasheed, Memoona; Hamza, Rifat; Acharya, Anushree; Ullah, Ehsan; Saqib, Muhammad Arif Nadeem; Abbe, Izoduwa; et al. (Hum Genet, 2018)
Identification of Mendelian genes for neurodevelopmental disorders using exome sequencing to study autosomal recessive (AR) consanguineous pedigrees has been highly successful. To identify causal variants for syndromic and non-syndromic intellectual disability (ID), exome sequencing was performed using DNA samples from 22 consanguineous Pakistani families with ARID, of which 21 have additional phenotypes including microcephaly. To aid in variant identification, homozygosity mapping and linkage analysis were performed. DNA samples from affected family member(s) from every pedigree underwent exome sequencing. Identified rare damaging exome variants were tested for co-segregation with ID using Sanger sequencing. For seven ARID families, variants were identified in genes not previously associated with ID, including: EI24, FXR1 and TET3 for which knockout mouse models have brain defects; and CACNG7 and TRAPPC10 where cell studies suggest roles in important neural pathways. For two families, the novel ARID genes CARNMT1 and GARNL3 lie within previously reported ID microdeletion regions. We also observed homozygous variants in two ID candidate genes, GRAMD1B and TBRG1, for which each has been previously reported in a single family. An additional 14 families have homozygous variants in established ID genes, of which 11 variants are novel. All ARID genes have increased expression in specific structures of the developing and adult human brain and 91% of the genes are differentially expressed in utero or during early childhood. The identification of novel ARID candidate genes and variants adds to the knowledge base that is required to further understand human brain function and development.
Keywords: Adult; Consanguinity; Family; Female; Genes, Recessive; Genetic Markers; Humans; Intellectual Disability; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree

Novel digenic inheritance of PCDH15 and USH1G underlies profound non-syndromic hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Acharya, Anushree; Liaqat, Khurram; Nickerson, Deborah A; Bamshad, Michael J; Shah, Khadim; Ahmad, Wasim; Leal, Suzanne M (BMC Med Genet, 2018)
BACKGROUND: Digenic inheritance is the simplest model of oligenic disease. It can be observed when there is a strong epistatic interaction between two loci. For both syndromic and non-syndromic hearing impairment, several forms of digenic inheritance have been reported. METHODS: We performed exome sequencing in a Pakistani family with profound non-syndromic hereditary hearing impairment to identify the genetic cause of disease. RESULTS: We found that this family displays digenic inheritance for two trans heterozygous missense mutations, one in PCDH15 [p.(Arg1034His)] and another in USH1G [p.(Asp365Asn)]. Both of these genes are known to cause autosomal recessive non-syndromic hearing impairment and Usher syndrome. The protein products of PCDH15 and USH1G function together at the stereocilia tips in the hair cells and are necessary for proper mechanotransduction. Epistasis between Pcdh15 and Ush1G has been previously reported in digenic heterozygous mice. The digenic mice displayed a significant decrease in hearing compared to age-matched heterozygous animals. Until now no human examples have been reported. CONCLUSIONS: The discovery of novel digenic inheritance mechanisms in hereditary hearing impairment will aid in understanding the interaction between defective proteins and further define inner ear function and its interactome.
Keywords: Adult; Animals; Cadherins; Hearing Loss; Heterozygote; Humans; Male; Mechanotransduction, Cellular; Multifactorial Inheritance; Mutation; Nerve Tissue Proteins; Pakistan; Pedigree; Usher Syndromes; Young Adult

A variant in LMX1A causes autosomal recessive severe-to-profound hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Liaqat, Khurram; Jan, Abid; Nasir, Abdul; Hussain, Shabir; Nickerson, Deborah A; Bamshad, Michael J; Ullah, Asmat; Ahmad, Wasim; Leal, Suzanne M (Hum Genet, 2018)
Hereditary hearing impairment is a common sensory disorder that is genetically and phenotypically heterogeneous. In this study, we used a homozygosity mapping and exome sequencing strategy to study a consanguineous Pakistani family with autosomal recessive severe-to-profound hearing impairment. This led to the identification of a missense variant (p.Ile369Thr) in the LMX1A gene affecting a conserved residue in the C-terminus of the protein, which was predicted damaging by an in silico bioinformatics analysis. The p.Ile369Thr variant disrupts several C-terminal and homeodomain residue interactions, including an interaction with homeodomain residue p.Val241 that was previously found to be involved in autosomal dominant progressive HI. LIM-homeodomain factor Lmx1a is expressed in the inner ear through development, shows a progressive restriction to non-sensory epithelia, and is important in the separation of the sensory and non-sensory domains in the inner ear. Homozygous Lmx1a mutant mice (Dreher) are deaf with dysmorphic ears with an abnormal morphogenesis and fused and misshapen sensory organs; however, computed tomography performed on a hearing-impaired family member did not reveal any cochleovestibular malformations. Our results suggest that LMX1A is involved in both human autosomal recessive and dominant sensorineural hearing impairment.
Keywords: Adolescent; Adult; Animals; Child; Disease Models, Animal; Ear, Inner; Female; Genes, Dominant; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; LIM-Homeodomain Proteins; Male; Mice; Mutation, Missense; Pedigree; Transcription Factors; Whole Exome Sequencing

A Syndromic Intellectual Disability Disorder Caused by Variants in TELO2, a Gene Encoding a Component of the TTT Complex. - You, Jing; Sobreira, Nara L; Gable, Dustin L; Jurgens, Julie; Grange, Dorothy K; Belnap, Newell; Siniard, Ashley; Szelinger, Szabolcs; Schrauwen, Isabelle; Richholt, Ryan F; Vallee, Stephanie E; Dinulos, Mary Beth P; et al. (Am J Hum Genet, 2016)
The proteins encoded by TELO2, TTI1, and TTI2 interact to form the TTT complex, a co-chaperone for maturation of the phosphatidylinositol 3-kinase-related protein kinases (PIKKs). Here we report six affected individuals from four families with intellectual disability (ID) and neurological and other congenital abnormalities associated with compound heterozygous variants in TELO2. Although their fibroblasts showed reduced steady-state levels of TELO2 and the other components of the TTT complex, PIKK functions were normal in cellular assays. Our results suggest that these TELO2 missense variants result in loss of function, perturb TTT complex stability, and cause an autosomal-recessive syndromic form of ID.
Keywords: Adolescent; Carrier Proteins; Child; Female; Humans; Intellectual Disability; Male; Molecular Chaperones; Pedigree; Phosphatidylinositol 3-Kinases; Protein-Serine-Threonine Kinases; Telomere-Binding Proteins